Diaphragmatic hernia transhiatal postsophagectomy. An exceptional complication - Oddone, Nicolás; Quiró Saldaña, Fernando; Crocci, Fabio; Henderson, Eduardo; Balboa, Oscar (Cirugía del Uruguay, 2005)
Post transhíatal esophagectomy díaphragmatíc hernia is an exceptional complication due to the poor survival in the long term of esophageal cancers and oligosymptomatic picture, whích renders its diagnosis difficult.